High-Energy Enteral Nutrition in Infants After Complex Congenital Heart Surgery - Ni, Ping; Chen, Xi; Zhang, Yueyue; Zhang, Mingjie; Xu, Zhuoming; Luo, Wenyi (Frontiers in Pediatrics, 2022)
Background: Malnutrition is common in complex congenital heart disease (CCHD). The purpose of this study was to compare the safety and efficacy of early initiation of high-energy enteral nutrition (EN) with regular energy EN in infants after surgery for CCHD. Methods: This is a subgroup analysis of a randomized controlled trial (RCT) which was conducted in the cardiac intensive care unit (CICU) of the largest pediatric heart center in China. 80 children with CCHD after surgery were from two groups, the intervention group (n=40) was given high-energy EN and the control group (n=40) was given regular energy EN. We analyzed the effects of the two interventions on outcomes such as caloric attainment rate, gastrointestinal intolerance, duration of mechanical ventilation, and anthropometry at discharge. Results: There was no difference in the daily milk intake between the two groups, but the calorie intake (50.2 vs. 33.4, P＜0.001), protein intake (1.1 vs. 0.9, P＜0.001) and caloric attainment rate were higher in the intervention group (77.5% vs. 45.0%, P=0.003). In addition, the incidence of pneumonia (P=0.003) and duration of mechanical ventilation (P=0.008) were less in the intervention group, and biceps circumference and triceps skinfold thickness at hospital discharge were greater than those in the control group (P＜0.001). We have not found statistical differences in gastrointestinal intolerance, glycemic fluctuations, incidence of pressure ulcers, length of CICU stay and postoperative hospital days between the two groups. Conclusions: Early initiation of high-energy EN may be safe and effective in infants after complex cardiac surgery. Low doses high-energy EN did not increase gastrointestinal intolerance or glycemic fluctuations and also improved post-operative nutrition by increasing caloric and protein intake without increasing fluid intake.